Development of e-business standards in engineering services. (25th September 2009) - Peterson, Rebecca; Wei, June; Yang, Jiaqin
The purpose of this paper is to develop electronic business standards for engineering services. Specifically, it first developed an electronic customer chain management conceptual model for the engineering services by integrating Information Technology (IT) with the customer-focused business processes in engineering services firms. Second, electronic business standards were developed based on the conceptual model. Third, current IT adoption rates within the engineering services industry were analysed by reviewing e-business applications in six dominant engineering services firms. The results of this research will be beneficial for accelerating IT adoption in the engineering services.